Experimental Study of Bioethanol Production as Fuel from Salacca Zalacca Waste and Coconut Water Waste Combination. (April 2019) - Idris, Muhammad; Novalia, Uun
Abstract: The process of burning fuel from the engine produces exhaust emissions that have a negative impact on the environment. Bioenergy as biofuel needs to develop to reduce emissions. Biomass is one of the bioenergy sources and has high potential to be used as a liquid fuel; some of the available biomass is a waste of salacca zalacca fruit and coconut water waste. In the process of bioethanol production, several mechanical factors influence it, including the energy needed for the distillate process, bioethanol mass flow rate and the ethanol content it contains. This research aims to analyze the energy needed for the distillation process to reach 85 OC, calculate the mass flow rate and determine the ethanol content of this fuel. An acquisition parallax microcontroller device is installed on the distillation vessel and condenser. This tool is used to record changes in temperature during the distillation process. From the experiments that have been done, the total energy needed for the distillation process is 346.32 W, bioethanol mass flow rate is 0.0665 kg / s